2012
DOI: 10.1371/journal.pcbi.1002555
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Free Energy Path of Ligand-Induced Transition in Adenylate Kinase

Abstract: Large-scale conformational changes in proteins involve barrier-crossing transitions on the complex free energy surfaces of high-dimensional space. Such rare events cannot be efficiently captured by conventional molecular dynamics simulations. Here we show that, by combining the on-the-fly string method and the multi-state Bennett acceptance ratio (MBAR) method, the free energy profile of a conformational transition pathway in Escherichia coli adenylate kinase can be characterized in a high-dimensional space. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
127
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 60 publications
16
127
1
Order By: Relevance
“…The most commonly used pair of order parameters for plotting 2D free energy surfaces of snapshots of simulation conformers is a heuristic measure consisting of the mass-center distances between domains (center of mass distance between the LID and CORE, and the center of mass distance between NMP and CORE) [24,58,[61][62][63][64][65][66]. Several studies use a LID-CORE and NMP-CORE angle pair, as shown in Figure 1, to independently quantify LID and NMP opening motions [15,31,59,67,68].…”
Section: Collective Variables Describing the Adk Transitionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most commonly used pair of order parameters for plotting 2D free energy surfaces of snapshots of simulation conformers is a heuristic measure consisting of the mass-center distances between domains (center of mass distance between the LID and CORE, and the center of mass distance between NMP and CORE) [24,58,[61][62][63][64][65][66]. Several studies use a LID-CORE and NMP-CORE angle pair, as shown in Figure 1, to independently quantify LID and NMP opening motions [15,31,59,67,68].…”
Section: Collective Variables Describing the Adk Transitionmentioning
confidence: 99%
“…Lou and Cukier [71], Brokaw and Chu [72], and Pontiggia et al [73] all measure NMP-CORE separation with the distance between residues 55 and 169, but each, respectively, monitor LID-CORE variation differently: LID-CORE mass-center distance [71], C Ī± distance between residues 127 and 194 [72], and LID-CORE angle [73]. Progress along one dimension (e.g., plotting the potential of mean force) was captured using domain mass-center distances [24,58,69,74], RMSD to and/or from crystal structures [15,61,67,75], and indices or distances along a computed reaction coordinate pathway [24,47,48,66,76,77]. …”
Section: Collective Variables Describing the Adk Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to apply this method to complex molecular systems, which is obviously the next step, it is indispensable to make a great use of parallel calculation techniques. For a future work, the authors are interested in studying the conformational change of adenylate kinase [39], for which the minimum free energy path was recently elucidated by the on-the-fly string method [40].…”
Section: Discussionmentioning
confidence: 99%